SOSIALISASI LITERASI DIGITAL GUNA MENINGKATKAN PEMAHAMAN DIGITAL PADA SISWA MA KALIFA NUSANTARA - NI Wayan Nanik Suaryani Taro Putri; Eka Grana Aristyana Dewi; Riszki Indika Pratama; Antonius Aston Delfan; wayan farrel ichiro; Gusti Ayu Komang Tari Kusuma Wardani; Tiara Kartini (LPPI UMN AL WASHLIYAH, 2026)
This community service study was conducted because students’ digital literacy was still low, which could lead to hoaxes, cyberbullying, misuse of personal data, and irresponsible social media behavior. The activity aimed to improve MA Kalifa Nusantara students’ understanding of data security, digital ethics, and the productive use of technology. The implementation was carried out offline through interviews with the school and the delivery of interactive materials, including lectures, demonstrations, videos, posters, and active discussion. It was then evaluated by comparing pre-test results from students who did not receive the socialization with post-test results from students who did. The results showed a significant improvement in understanding, indicated by an increase in the average score from 76.17% in the pre-test group to 93.36% in the post-test group, reflecting a real positive change in students’ daily digital literacy practices. The greatest improvement was found in the ability to distinguish true and suspicious news, with an increase of 24.74%. Therefore, a structured and interactive digital literacy program proved effective in improving students’ knowledge, awareness, and wise attitudes in using the internet and social media.